Fireboat : the heroic adventures of the John J. Harvey - Kalman, Maira (New York : G.P. Putnam's Sons, 2002)
A fireboat, launched in 1931, is retired after many years of fighting fires along the Hudson River, but is saved from being scrapped and then called into service again on September 11, 2001.
4.2
K-3.
Keywords: John J. Harvey (Fireboat) -- Juvenile literature; World Trade Center (New York, N.Y.) -- Juvenile literature; John J. Harvey (Fireboat); World Trade Center (New York, N.Y.); John J. Harvey (Fireboat); World Trade Center (New York, N.Y.); September 11 Terrorist Attacks, 2001 -- Juvenile literature; Boats and boating; Fire extinction; September 11 Terrorist Attacks, 2001.; Boats and boating; Fire prevention; September 11 Terrorist Attacks, 2001.